A Descriptive Study on Registered Nurses' Continuing Educational Needs in Research from Three Different Health Care Institutes in Singapore. (June 2015) - Ang, Shin Yuh; Kwan, Xui Ling; Aloweni, Fazila Abu Bakar; Aw, Ai Tee; Tan, Ai Meng; Chua, Alice Foong Sin; Tay, Rosaline Lee Hua
Introduction: Nurses are encouraged to engage in research activities in order to stay abreast with the current nursing practice. However, limited knowledge about the research process may influence their level of involvement and utilisation of research in their daily nursing practices. This study examines Singapore nurses' perceived knowledge and educational needs in research as well as to explore their preferred mode and duration of education delivery. Methods: This is a multi-site, cross-sectional study that recruited 2248 registered nurses working in Singapore. A self-administered tool was used to examine nurses' perceived knowledge and educational needs in research. Descriptive statistics were used to present the nurses' demographic data; the Kruskal-Wallis and chi-square tests were used to examine the relationship between the nurses' education level and their perceived knowledge and educational needs in research. Results: Nurses in this study perceived low levels of knowledge in research. Majority of those who were involved in research activities had a bachelor's degree. There were statistically significant differences between education level and perceived knowledge (p=0.001). However, there was no significant difference between education level and perceived educational needs. Younger nurses (19–35 years old) preferred shorter duration when attending workshops compared to older nurses (36 years old and above). Skill-based workshop and tutorial or seminar that last no longer than a week was the most preferred educational mode and duration. Conclusion: Nurses with high level of education perceived a higher level of research knowledge and thus reported lower educational needs in research. The results showed the need for continual training programs, even for nurses with bachelor's and master's degrees, in order to better prepare them for evidence-based practice. Understanding the demographic of the nurses and their learning styles is important when devising strategies to teach research.